Reliability analysis of the Manchester Triage System: inter-observer and intra-observer agreement - Cristiane Chaves de Souza; Tânia Couto Machado Chianca; Welfane Cordeiro Júnior; Maria do Carmo Paixão Rausch; Gabriela Fontoura Lana Nascimento (Universidade de São Paulo, 2018)
ABSTRACT Objective: To analyze the reliability of the Manchester Triage System to determine the priority of patients in emergency services. Method: This is a reliability study with a sample of 361 nurses. The data were collected in three stages and the questionnaires were applied using the electronic software. The agreement was measured by the evaluation of clinical cases. The outcomes evaluated were agreement with the gold standard and intra-observer in the indication of the flowchart, discriminator, and level of risk. Data were submitted to univariate and bivariate analyses. The agreement was measured by the Kappa index. Results: The external and internal reliability of the protocol ranged from moderate to substantial (Kappa: 0.55-0.78). The time of professional experience as a nurse, in emergency services and in the classification of risk were associated with external and internal reliability. The correct choice of the discriminator influenced the correct indication of the risk level (R² = 0.77, p <0.0001) more than the correct choice of the flowchart (R² = 0.16, p <0.0001). Conclusion: The reliability of the Manchester Triage System ranged from moderate to substantial and it was influenced by the clinical experience of the nurse. The protocol is safe for defining clinical priorities using different classification flowcharts.